Strategi Pembelajaran Di Era Digital : Tantangan Profesionalisme Guru Di Era Digital - Heru Siswanto (Darajat: Jurnal Pendidikan Agama Islam, 2020)
The use of technology by humans at this time is very helpful in completing various jobs is something that is a necessity in life. Two sides that should complement each other include the development of this technology, it should also be followed by developments in human resources (HR) that are increasingly advanced and civilized based on the value of policy relations. In more detail in this content, the development of technology and communication in the field of education, according to Rosenberg, with this development there are five shifts in the learning process, namely from training to appearance, from the classroom to where and whenever, from paper to online or channels, facilities physical access to network facilities, from cycle time to real time. And technological developments which then have a positive impact on the world education system regulation, where currently there is e-learning, namely the teaching of learning in a broad range with a foundation based on three criteria including e-learning is a network with the ability to update, store, distribute and share material or information. With the system, sending up to the last user through a computer using standard internet technology. Among several teaching strategies in the form of e learning include: Learning by doing, Incidental learning, Learning by reflection, Case-based learning, Learning by exploring